Lush life - Price, Richard 1949- (Farrar, Straus and Giroux, 2008)
In this first-rate police procedural, Eric Cash, the 34-year-old bartender at Café Berkmann and a would-be screenwriter, ends up in jail as a murder suspect and it's up to two New York City police detectives to find out the truth